First Timers and Old Timers : The Texas Folklore Society Fire Burns On - Untiedt, Kenneth L., 1966- (Book collections on Project MUSE., 2012)
The Texas Folklore Society has been alive and kicking for over one hundred years, and there's hardly any mystery as to what keeps the organization going strong. The secret to its longevity is simply the constant replenishment of its body of contributors. We are especially fortunate in recent years to have had papers given at annual meetings by new members - young members, many of whom are college or even high school students. These presentations are oftentimes given during sessions right alongside some of the oldest members. The society has also had long-time members who have been around for years, but had never yet given papers; thankfully, they finally took the opportunity to present their research, fulfilling the mission of the TFS: to collect, preserve, and present the lore of Texas and the Southwest.